Integrated Wastewater and Waste Heat Recovery System in Coal-Fired Power Plants Using Reverse Osmosis to Produce Clean Water and Increase Thermal Efficiency - Vincentius Adven Brilian; Sasa Aulia; Farah Octaviani; Thariq Arian Khalfani (Purnomo Yusgiantoro Center, 2022)
Indonesian electricity supply is still dominated by coal-fired power plants (CPP) by more than 50%. Water consumption for CPP in Indonesia reaches 222 million kL/year. Meanwhile, 10% of Indonesia's population is predicted to experience a clean water crisis in 2045. Most of the water consumed by CPP will be disposed of as wastewater, such as cooling tower blowdown and boiler blowdown. Boiler blowdown temperature is still relatively high. Thus, it wastes a high-quality of energy. Therefore, these conditions open the opportunity for innovations in improving clean water supply and increasing CPP’s thermal efficiency. In this research, a novel system that integrates wastewater recovery and waste heat recovery in CPP using reverse osmosis is proposed to produce clean water while increasing the CPP’s thermal efficiency. In this system, the boiler blowdown is streamed to a heat exchanger as the feedwater preheater. Then, the boiler blowdown flows to a Pelton turbine to generate electricity. The boiler blowdown will then be mixed with the cooling tower blowdown and streamed to a reverse osmosis system to produce clean water. The brine is converted by an electrolyzer into NaClO and H2. Thermodynamic and economic analyses are performed to assess the proposed system’s technical and economic feasibility. Based on the thermodynamic analysis calculation using the Engineering Equation Solver, the system is able to produce 162 kL/hr of clean water and the thermal efficiency of the coal-fired power plant increases by 0.4%. The economic analysis showed that the additional system is feasible with a payback period of 4.9 years.